Biosorption Copper (Cu) and Mercury (Hg) by Omphalina sp. using Batch, Rotary, Biotray, and Pack Bed Flow Methods - Desi Purwaningsih; I Made Artika; Tri Panji; Suharyanto Suharyanto (Current Biochemistry, 2016)
Heavy metal waste treatment often uses dangerous chemicals. Omphalina sp is a nonpathogenic fungi that can be used to reduce the harmful effects of waste treatment. The use of fungal biomass has advantages such as low operating costs, efficient, and high metal binding capacity, minimal sludge, metals can be recovered, biosorbent can be regenerated, raw materials available easily, can use inactivated microorganism, and does not require additional nutrients. In the present study optimization of the biomass utilization for waste water treatment was conducted by comparing batch, rotary, packbed flow, and biotray methods. Results showed that Omphalina sp can reduce mercury level up to 91.38% with rotary, 83.98% with biotray, 87.14% with pack bed flow, and 31.94% with batch methods respectively from initial Hg concentration of 3 ppm. Similarly, Omphalina sp can reduce copper level up to 23.58% with rotary, 22.66% with biotray, 10.53% with pack bed flow, 10.17% with batch methods respectively from initial Cu concentration of 100 ppm. Optimum absorption Hg and Cu occurs in the first one hour.